Nexus Between Crude Oil, Gold Prices, Commodity Prices And Stock Market In India At Times Of Covid -19 - Sapra, Prof. Ritu; Gupta, Dr. Rishabh (Migration Letters, 2024)
The present paper tries to analyze the relationship between crude oil, gold, commodity prices, and the Indian stock market at a time of the pandemic. The study includes various variables particularly Brent crude oil prices as a proxy for crude, gold price future as a proxy for the gold price while MCX is being chosen as a proxy for the commodity price. The study adopts a series of time series techniques like unit root testing, Johansen cointegration for the measurement of long-run relationship, VECM for checking the short-run equilibrium amongst the select variables, Granger causality test followed by Variance decomposition test for the measurement of the degree of exogeneity amongst the variables. The findings of the paper depicts the presence of a long-run relationship between the select variables and the stock market index. Further, there is a long-run causality on a market index derived from gold, commodity, and crude oil prices while short-run causality is being derived only from gold but not from commodity, crude oil, and the lag from the market index itself. Also, the Market index granger causes Commodity and crude oil but, the gold, crude, and commodity index do not granger cause the market index. The results of a Variance decomposition test show that market index and gold are more exogenous in comparison to commodity and crude oil prices. The study will assist the investors and policymakers in diversifying their portfolios by analyzing the impact of particular variables on the stock market.